Ultrahigh cyclic stability and giant elastocaloric effect in directionally solidified (Ni50Mn28Fe2.5Ti19.5)99.4B0.6 alloy. (May 2023) - Guan, Ziqi; Bai, Jing; Zhang, Yu; Gu, Jianglong; Zhang, Yudong; Esling, Claude; Zhao, Xiang; Zuo, Liang
ABSTRACT: Cyclic stability of elastocaloric materials is critically important for practical applications in solid-state refrigeration. Ni-Mn-based Heusler-type alloys exhibit a large elastocaloric response to low driving stress. However, these alloys can only be worked for short-term cyclic operation due to their intrinsic brittleness. Here, we demonstrate the achievement of giant elastocaloric effect (eCE) and long-term fatigue performance in a directional solidification (Ni50 Mn28 Fe2.5 Ti19.5 )99.4 B0.6 alloy. At 303 K, the maximum compressive strength and strain of the alloy can be as high as 2734 MPa and 20.5%, respectively. During fast loading and unloading with the stress of 435 MPa and the strain of 8%, giant adiabatic temperature change (ΔTad ) of 25.1 K and -24.5 K can be obtained, respectively. In particular, a large ΔTad of about 5.8 K is generated during cycling at 360 MPa stress and 3.5% strain, and can be maintained for more than 20, 000 cycles. Graphical abstract: Image, graphical abstract